Game developemnt 2042 : the future of game design, development, and publishing - Fields, Tim (CRC Press / Taylor & Francis Group, 2023)
"This book explores the future of game design, development, and publishing, extrapolating the next two decades through the lens of the industry's evolution over the last ten years and the technical advances in recent adjacent markets"-- Provided by publisher